2017
DOI: 10.1080/0158037x.2017.1310096
|View full text |Cite
|
Sign up to set email alerts
|

Understanding adult lifelong learning participation as a layered problem

Abstract: This paper discusses the layered nature of lifelong learning participation, bringing together fragmented insights in why adults do or do not participate in lifelong learning activities. The paper will discuss the roles and responsibilities of individual adults, education and training providers and countries' social education policies, often labelled as the micro, meso and macro level. The aim of this work is to add a new model to the knowledge base that attempts to integrate separate insights at the three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0
25

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 35 publications
4
56
0
25
Order By: Relevance
“…The PIAAC data also provides a sound foundation for our explorative comparisons between the four Nordic countries, applying the perspective of the BAM. Indeed, a recent wave of research (Boeren, 2017;Boeren & Holford, 2016;Lavrijsen & Nicaise, 2017;Massing & Gauly, 2017;Rothes, Lemos & Goncalves, 2017) calls for the importance of understanding the role of structural factors and institutional settings of the country or countries in question, also in case of low-skilled (Brown & Bimrose, 2018;Zanazzi, 2018) and non-participants (Becker Patterson, 2018;Roosmaa & Saar, 2017). The study by Boeren Holford (2016) found that the worker's country explained participation even stronger than individual characteristics (e.g., age, gender, education and occupation).…”
Section: The Bounded Agency Modelmentioning
confidence: 99%
“…The PIAAC data also provides a sound foundation for our explorative comparisons between the four Nordic countries, applying the perspective of the BAM. Indeed, a recent wave of research (Boeren, 2017;Boeren & Holford, 2016;Lavrijsen & Nicaise, 2017;Massing & Gauly, 2017;Rothes, Lemos & Goncalves, 2017) calls for the importance of understanding the role of structural factors and institutional settings of the country or countries in question, also in case of low-skilled (Brown & Bimrose, 2018;Zanazzi, 2018) and non-participants (Becker Patterson, 2018;Roosmaa & Saar, 2017). The study by Boeren Holford (2016) found that the worker's country explained participation even stronger than individual characteristics (e.g., age, gender, education and occupation).…”
Section: The Bounded Agency Modelmentioning
confidence: 99%
“…These perspectives have become a basis for building more developed comprehensive understandings of participation which incorporate the influence of factors at different levels and which are relevant for comparative research (e.g., Rubenson and Desjardins 2009;Boeren 2017;Lee 2018). By labelling their model "Bounded Agency", Rubenson and Desjardins (2009) wish to refer to the fact that adults have agency to decide on participation to education or training, however, due to bounds, or restrictions, they cannot take the preferred action to participate.…”
mentioning
confidence: 99%
“…More specifically, they focus on the interaction between structurally and individually based barriers to participation in adult education. Boeren (2017) sees the participation in AL as a layered problem. Given this, she proposes an understanding of AL as an interplay between different actors: (i) the participants with their intentions, needs, attitudes and other behavioural characteristics as well as their personal characteristics such as gender, age, income and social/ cultural capital; (ii) the educational institutions and workplaces being the major learning providers; and (iii) the social policy adopted in the countries where the participants live.…”
mentioning
confidence: 99%
“…Education level achieved . Following the classic theories of Merton (1976) and Bourdieu (1984), researchers (Boeren, 2017; Rubenson, 2018) have referred to the so-called “Matthew effect,” according to which individuals who have achieved a higher level of education tend to seek or be more apt to learn even more. These learners have stronger predispositions toward learning gained from their previous studies, and consequently, they profit more greatly from additional training or instruction.…”
mentioning
confidence: 99%